ETDRS panretinal photocoagulation combined with intravitreal ranibizumab versus PASCAL panretinal photocoagulation with intravitreal ranibizumab versus intravitreal ranibizumab alone for the treatment of proliferative diabetic retinopathy - Barroso,Rafael de Montier P. (2020)
ABSTRACT Purpose: To compare visual acuity, macular thickness, and the area of active neovascularization based on fluorescein angiography outcomes associated with standard single-spot panretinal photocoagulation in the Early Treatment Diabetic Retinopathy Study (ETDRS) pattern combined with intravitreal ranibizumab injection versus multiple-spot full scatter (PASCAL) panretinal photocoagulation combined with intravitreal ranibizumab injection versus intravitreal injection alone in patients with proliferative diabetic retinopathy. Methods: Patients with proliferative diabetic retinopathy and no prior laser treatment were randomly assigned to receive three different types of treatment. Panretinal photocoagulation in the ETDRS group was administered in two sessions (weeks 0 and 2), and panretinal photocoagulation in the PASCAL group was administered in one session (week 0). Intravitreal injection of ranibizumab was administered at the end of the first laser session in both the ETDRS and PASCAL groups and at week 0 in the intravitreal injection group. Comprehensive ophthalmic evaluations were performed at baseline and every 4 weeks through week 48. Results: Thirty patients (n=40 eyes) completed the 48-week study period. After treatment, best-corrected visual acuity was significantly (p<0.05) improved at all follow-up visits in the group receiving intravitreal injection alone, at all but week 4 in the ETDRS group, and at all but weeks 4 and 8 for the PASCAL group. A significant decrease in central subfield macular thickness was observed in the PASCAL group at weeks 4, 8, and 48; only at week 48 in the intravitreal injection group; and never in the ETDRS group. There was no significant difference among the three treatment groups with respect to change from baseline to week 48 in best-corrected visual acuity, central subfield macular thickness, or fluorescein leakage from active neovascularization in best-corrected visual acuity, central subfield macular thickness, or fluorescein leakage from active neovascularization. Conclusions: Intravitreal injection alone or combined with single- or multiple-spot panretinal photocoagulation yielded similar outcomes with respect to mean change in best-corrected visual acuity, central subfield macular thickness, and fluorescein leakage from active neovascularization at up to one-year of follow-up. All subjects provided written informed consent to participate (NCT02005432 in clinicaltrials.gov).